2017
DOI: 10.1200/jco.2016.70.7158
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Postmastectomy Radiation Therapy Is Safe and Effective: First Results From a Prospective Phase II Trial

Abstract: Purpose Conventionally fractionated postmastectomy radiation therapy (PMRT) takes approximately 5 to 6 weeks. Data supporting hypofractionated PMRT is limited. We prospectively evaluated a short course of hypofractionated PMRT, in which therapy was completed in 15 treatment days. Patients and Methods We delivered PMRT at a dose of 36.63 Gy in 11 fractions of 3.33 Gy over 11 days to the chest wall and the draining regional lymph nodes, followed by an optional mastectomy scar boost of four fractions of 3.33 Gy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 37 publications
8
69
1
Order By: Relevance
“…9,14 More recently, results from a Phase II trial of 69 patients treated with hypofractionated PMRT in the US demonstrated that hypofractionated PMRT may be safe and effective. 15 The favorable results from this trial have provided the impetus for the development of a Phase III randomized trial – Alliance A221505 – which seeks to compare outcomes following hypofractionated PMRT versus standard fractionation PMRT in a large cohort of women.…”
Section: Introductionmentioning
confidence: 99%
“…9,14 More recently, results from a Phase II trial of 69 patients treated with hypofractionated PMRT in the US demonstrated that hypofractionated PMRT may be safe and effective. 15 The favorable results from this trial have provided the impetus for the development of a Phase III randomized trial – Alliance A221505 – which seeks to compare outcomes following hypofractionated PMRT versus standard fractionation PMRT in a large cohort of women.…”
Section: Introductionmentioning
confidence: 99%
“…In the START A/B trials, 491 patients had a mastectomy and received hypofractionated postmastectomy radiotherapy (HF-PMRT). The first prospective phase II study on HF-PMRT was recently published in May 2017 [10] showing promising results. The same group is carrying out the Alliance A221505 study, a phase III randomized trial of HF-PMRT following breast reconstruction.…”
Section: Hypofractionated Radiotherapymentioning
confidence: 99%
“…In most recent study conducted by Khan et al and published in journal of clinical oncology, which was a phase II prospective study offered one of the shortest courses of post mastectomy hypo fractionated radiotherapy delivered in eleven fractions to the chest wall and regional nodes with fifteen fractions inclusive of a boost, they demonstrated low toxicity and high local control with this regimen but they finally reported that these are more robustly tested and described in breast cancer than in any other human malignancy and still, they do not believe these shorter schedules should be used routinely off study, particularly among women with breast reconstruction [16].…”
Section: Safety Of Hypo Fractionation In Breast Cancermentioning
confidence: 99%
“…AllianceA221505, a randomized phase III trial of post mastectomy hypo fractionated radiotherapy in which it will test the safety of a shorter course schedule (42.56 Gy in 16 fractions) compared to conventional fractionation, all women in this trial will have breast reconstruction or intent for ultimate reconstruction. The primary end point of this trial is reconstruction complication rate and secondary end points will include lymph edema, toxicities including brachial plexopathy, recurrence-free survival, and end points for health costs/economics [16].…”
Section: Future Directionsmentioning
confidence: 99%